Avaliação do método da quebra do grafite para estimação da sensibilidade de transdutores piezelétricos utilizados na técnica da Impedância Eletromecânica - Almeida, Vinicius Augusto Dare de [UNESP] (2015)
This dissertation presents a comparative study of the sensitivity of different types of piezoelectric transducers for damage detection in structural health monitoring (SHM), systems, based on the electromechanical impedance (EMI) technique. A comparison of three piezoelectric transduces was performed: PZT (Pb-Lead Zirconate Titanate) ceramic, MFC (Macro-Fiber Composite) device and piezoelectric diaphragm, also known as buzzer. The experimental evaluation of the sensitivity of the PZT and MFC transducers was performed in an alternative way using the pencil lead break (PLB) method, which is very simple and used in a acoustic emission (AE) systems. It is based on the break of a lead against the structure to be analyzed. The tests were carried out on aluminum beams of different sizes. The structural damage was induced by metallic mass (steel nts), which were fixed in the beams with cyanoacrylate glue. The evaluation of the results was made by comparing de damage indices obtained from the electrical impedance signatures of the PZT and MFC transducers coupled to the structure to be analyzed and the power spectral density (PSD) calculations obtained using the PLB and the Welch method. The experimental results indicated that the transducers have different sensitivities for the detection of damage, which also depend on the frequency range. The conclusion is that the results showed a good relationship between the damage indices and the PSD, indicating that the PLB method can be a useful tool to estimate the sensitivity in damage detection applications based on the EMI technique